Model Regresi Ordinal pada Analisis Determinan Status Gizi Balita Usia 6–59 Bulan - Indria Nuraini; Yuni Khoirul Waroh; Solicha Solicha (STIKES Mamba'ul 'Ulum Surakarta, 2026)
Background: The nutritional status of toddlers remains a public health issue that affects growth, development, and the quality of human resources. Various biological factors and health behaviours are suspected to influence toddler nutritional status, but evidence regarding the dominant influencing factors remains mixed.Research Objective: To analyse the determinants influencing the nutritional status of toddlers aged 6–59 months.Methods: The study used a quantitative, observational, cross-sectional design. The study sample consisted of 48 toddlers selected using a total sampling technique. Independent variables included age, sex, birth weight, nutritional intake, and history of exclusive breastfeeding, while the dependent variable was the toddler's nutritional status, assessed by the weight-for-age (BW/A) Z-score. Data were collected using questionnaires, KIA books/medical records, 24-hour food recalls, and anthropometric measurements. Data were analysed using univariate and multivariate methods using ordinal regression.Research results: showed that male gender (p=0.016; OR=0.162), nutritional intake in the deficit category (p=0.044; OR=0.044), and a history of not receiving exclusive breastfeeding (p=0.006; OR=10.85) significantly influenced toddler nutritional status. The Nagelkerke value of 0.558 indicates that the model explains 55.8% of the variation in toddler nutritional status.Conclusion: Toddler nutritional status is influenced by gender, nutritional intake, and a history of exclusive breastfeeding.Recommendations: Strengthen nutrition education, promote exclusive breastfeeding, and monitor toddler growth continuously.